The Impact of Screen Time on Mental Health Outcomes among Adolescents: A Systematic Literature Review - Naima Lassie; Ertati Suarni; Jean Henry Raule (PT. Anagata Sembagi Education, 2026)
Adolescence is a critical developmental period in which mental health trajectories are shaped by biological, social, and environmental influences, including pervasive digital technology use. This systematic literature review synthesizes evidence from twenty-five peer-reviewed studies published between 2021 and 2026 examining associations between screen time and mental health outcomes among adolescents aged ten to nineteen years. Following a structured search of PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar, studies were screened against predefined eligibility criteria covering observational, longitudinal, and review-level evidence with verifiable digital object identifiers. The synthesis indicates that higher total screen time, particularly social media or smartphone use exceeding roughly two hours daily, is consistently associated with elevated depressive symptoms, anxiety, sleep disturbance, and diminished well-being, although effect sizes are generally small to moderate, non-linear, and moderated by content type, use context, gender, and family communication patterns. Passive, comparison-driven use appears more detrimental than active, socially connective use, and dose-response or threshold effects emerge across several large cohort studies. This review's novelty lies in integrating recent 2024-2026 prospective cohort and umbrella-review evidence within a content-and-context framework rather than treating screen time as a single undifferentiated exposure. Implications for clinicians, parents, educators, and policymakers are discussed alongside methodological limitations, including reliance on self-reported screen time and heterogeneous outcome measures.